The politics of cultural performance. - Parkin, David J.; Caplan, Lionel; Fisher, Humphrey J. (Berghahn Books, 1996)
The line between what is regarded by people as "traditional" and "modern" is constantly being altered by new configurations of power. These essays examine the ways in which such changes are both communicated and created through cultural performances in diverse ethnographic settings. Examples are drawn from a wide range of forms and expressions: divinatory sequences, spirit possession rites, state ceremonials, village feasts, pilgrimages, language-use and craft specialisms. It was Abner Cohen, to whom this volume is dedicated, who first suggested that a dialectical relationship existed between power and symbolism. This concept, as developed in his seminal work, has since become a growing area of study as reflected in this important collection. By questioning some of the directions, the authors make a major interdisciplinary contribution to the study of cultural performance as a key factor in power relationships. The principal stage is Africa, but comparative ethnographic data are drawn from Ireland, Italy, South Asia, and the United Kingdom -- Présentation de l'éditeur.